Modeling of CFRP strengthened RC beams using the SNSM technique, proposed as an alternative to NSM and EBR techniques - Adel Boulebd; Ferhoune Noureddine; Boukhezar Mohcene; Habib Abdelhak Mesbah (Fracture and Structural Integrity)
In this paper, an analytical and numerical study in FEM finite element by the ABAQUS software was conducted. Which aims to study the behaviour of RC beams bending strengthened with SNSM side near surface mounted technique, proposed as a solution to avoid the failure mode by debonding of the strengthening, the disadvantage of the EBR externally bonded reinforced technique, and the failure mode by separation of the concrete cover relative to the NSM near surface mounted technique, by comparing the behaviour of the three techniques, the effect of the quantity of strengthening and confirm the results with the literature. The results of this study show that the numerical and analytical model can predict the behaviour of strengthened RC beams according to the three techniques, a clear improvement of the bending capacity of beams strengthened is noticed. A good preservation of the ductility of SNSM beams with a better failure mode.